An example to illustrate the role of R&D in the emerging industrial hydrogen economy - Foyer Jean; Proust Christophe; Proust Matthieu (MATEC Web of Conferences, 2023)
The global warming awareness, the reduction of fossil resources, the demand for well-being of industrialized societies, geopolitical upheavals and tomorrow perhaps the biodiversity crisis are powerful drivers to forster a change in the means of production and use of energy. In this context, the idea of a “hydrogen economy” emerged at the turn of the century (Brandon and Kurban, 2017) around the relatively new notion of hydrogen as an “energy carrier”. However, all concepts even if very appealing, become concrete achievements. Conditions for the emergence of an “industrial sector” (Stoffaës, 1980) need to be fulfilled, i.e. at least a viable market, robust technologies for production and use technologies and logistics. In the following, the authors attempt to illustrate the conditions for the emergence of an industrial hydrogen-energy sector, in particular the role of R&D that underpins this process. There is first a cognitive barrier. The physico-chemical properties of hydrogen are particularly well known, and means are available to produce it in large quantities (Brandon and Kurban, 2017). The risks are also known but are well under control in the industry. Socio-economic actors may find this reassuring. The second element is societal. Mature industrial sectors represent considerable fixed capital. Even if research has already shown that it would be possible to produce hydrogen differently, there is little reason for these well-established sectors to evolve without additional incentives. The societal “drivers” mentioned above (climate change, depletion of fossil resources, etc.) have prompted Europe to take increasingly restrictive measures on the consumption of fossil resources (carbon tax, anti-pollution standards). The effect is a paradigm shift, particularly for the mobility sector, which is now investing heavily in electric and hydrogen vehicles. The third element is techno-economic. If hydrogen appears as a possibility, it is because preliminary R&D work has developed key technologies: fuel cells, very high pressure tanks and created “demonstrators”. But the production technologies and the supply chain need to be developed. European regulations require the provision of hydrogen (produced in a renewable way) up to 3T per day every 150 km by 2030 (European parliament; 2021), which suggests a tight network of the territory. One option is local production either through water electrolysis or biomass gasification. QAIROS Energies identified a business model that can link significant local hydrogen use to favorable agricultural conditions. Technologies are available to grow the biomass, to pyrolyze/ gasify it and to turn the gases in hydrogen (Cao et al., 2020), which offers a range of possible processes. The economic equilibrium requires that the gasification yield be 75-125 kg H2 / ton of biomass with a minimum consumption of utilities (water, energy, consumables,...) and requires also as little residues and toxics as possible, the gas treatment costs being quickly prohibitive. Based on these constraints, QAIROS-Energies set up an R&D team aggregating skills in agronomy to select the most suitable crops, biomass pre-treatment (drying, grinding) and pyrogasification and gas treatment. The objective is to remove the obstacles and to demonstrate the feasibility of the project. For the pyro-gasification and gas treatment steps, a pilot was quickly set up (Figure 4) showing a certain resemblance to the future industrial units, which goes beyond academic habits.